Characterization of gray matter atrophy following 6-hydroxydopamine lesion of the nigrostriatal system. (15th October 2016) - Westphal, Robert; Sumiyoshi, Akira; Simmons, Camilla; Mesquita, Michel; Wood, Tobias C.; Williams, Steve C.R.; Vernon, Anthony C.; Cash, Diana
Highlights: Unilateral 6-OHDA lesioned rat model features brain structural changes resembling those in advanced Parkinson's disease. 6-OHDA-induced atrophy in the cortex is accompanied by a loss of cortical TH+ fibers. Structural changes were observed in both hemispheres in this unilaterally lesioned rat model. Abstract: Background: The unilaterally-lesioned 6-hydroxydopamine (6-OHDA) rat is one of the most commonly used experimental models of Parkinson's disease (PD). Here we investigated whether magnetic resonance imaging (MRI) that is widely used in human PD research, has the potential to non-invasively detect macroscopic structural brain changes in the 6-OHDA rat in ways translatable to humans. Methods: We measured the gray matter (GM) composition in the unilateral 6-OHDA rat in comparison to sham animals using whole-brain voxel-based morphometry (VBM) – an unbiased MR image analysis technique. The number of nigral dopamine (DA) neurons and the density of their cortical projections were examined post-mortem using immunohistochemistry. Results: VBM revealed widespread bilateral changes in gray matter volume (GMV) on a topographic scale in the brains of 6-OHDA rats, compared to sham-operated rats. The greatest changes were in the lesioned hemisphere, which displayed reductions of GMV in motor, cingulate and somatosensory cortex. Histopathological results revealed dopaminergic cell loss in the substantia nigra (SN) and a denervation in the striatum, as well as in the frontal, somatosensory and cingulate cortices. Conclusion: Unilateral nigrostriatal 6-OHDA lesioning leads to widespread GMV changes, which extend beyond the nigrostriatal system and resemble advanced Parkinsonism. This study highlights the potential of structural MRI, and VBM in particular, for the system-level phenotyping of rodent models of Parkinsonism and provides a methodological framework for future studies in novel rodent models as they become available to the research community.